Optimizing 21st-Century Skills through Marketplace Activity and Grouping Variations in Islamic Religious Education - Amelia Khoirunisa; Moh. Faizin; Alaika M. Bagus Kurnia PS; Wiwin Luqna Hunaida; Usman Yudi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
slamic Religious Education learning is still often teacher-centered, limiting students’ active participation and the development of 21st-century skills. This study aims to analyze how the Marketplace Activity (MPA) model and variations in grouping strategies foster the four Cs (communication, collaboration, critical thinking, and creativity) in Islamic Religious Education classrooms. Using a qualitative case study design at a public senior high school in Sidoarjo, data were collected through observations, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings show that MPA promotes dynamic and meaningful learning interactions. Heterogeneous groups encourage diverse ideas, dialogic exchange, and critical reflection, while homogeneous groups support task efficiency and clarity of roles. The four Cs emerged as Islamic value-based learning outcomes: value-driven collaborative communication, spiritual-intellectual collaboration, reflective faith-based reasoning, and integrative Islamic creativity. This study concludes that MPA has strong potential as an integrative learning model that connects cognitive skill development with spiritual character formation, making Islamic Religious Education more relevant to the competence and morality demands of the 21st century. Practically, teachers are encouraged to design student-centered activities, apply flexible grouping structures aligned with learning objectives, and integrate faith-based values with higher-order thinking to strengthen both academic and spiritual outcomes.